O Corpo em Mutação - Manuel-Cardoso, Pedro (Trabalhos de Antropologia e Etnologia, 2020)
The human being has been explained by science, as a “chemical and biological,” or as a “social and cultural”. This dualism has led to the impasse created by the Nature/Culture dichotomy and Individual/Society, today, again repeated by D.Sperber-P.Descola-T.Ingold-B.Latour and others. However, advances in knowledge have come to question this duality that anthropology did not know how to solve. And challenge the question Kant founder of Anthropology: “what is being human?”. This Conference seeks to answer the question: «The current mutation of Human body by science changes the concept of human being?». The response interferes with the current Theory of Human Evolution, and questions the Darwinian Adaptation while explanatory argument.